Future Time Perspective and its Motivational Relevance in Different Educational Contexts - Herrera Paredes, Dora Isabel (2019)
This study aims at systematizing and integrating research findings about Future Time Perspective (FTP) in Peruvian educational contexts. FTP is a motivational psychological variable that allows explaining the present behavior, considering goals set in the future.  The construct demonstrated its theoretical and empirical strength in different contexts. During the second half of the XXth Century Nuttin and Lens (1985) applied the variable in different fields, especially the educational one. Their proposal considered the cognitive and motivational properties of FTP; its density, extension and level of realism was then reported. Empirical research has been conducted to date under this theoretical background; however, a decade ago this concept was redirected to a multidimensional proposal conceptualized as Future Orientation (FO) considering three components: motivational, cognitive and behavioral (Seginer, 2009).In Peru, longitudinal and cross-sectional studies were carried out since 1998. These studies consistently documented that adolescents and youngsters studying in different educational institutions, showed a short FTP, a low level of realism and a keen aspiration for becoming professionals. During the last years, FO measuring was reoriented considering the multidimensional feature of the concept. Recent research findings in Peruvian adolescents and youngsters indicate that there is a positive and intense relation between satisfaction with life and the motivational component of FO. Taking into account these results, researchers consider that it is important to develop this line of investigation, as the analysis of the youngster’s motivation and FO will provide the guidelines for future social interventions in favor of their social insertion and well-being.